Serum ANCA and Overall Mortality: A 10-Year Retrospective Cohort Study on 1,024 Italian Subjects - Brunetta, Enrico; Ramponi, Giacomo; Folci, Marco; De Santis, Maria; Morenghi, Emanuela; Vanni, Elena; Bredi, Elena; Furlan, Raffaello; Angelini, Claudio; Selmi, Carlo (Frontiers in Immunology, 2021)
Background Antineutrophil cytoplasmic antibodies (ANCA) are primarily involved in the pathogenesis of ANCA-associated vasculitides (AAV). However, ANCA may also be present in healthy subjects and in patients with autoimmune disorders different from AAV. We hypothesized that serum ANCA are associated with a worse prognosis in disorders other than AAV. Objective We investigated the association between the overall survival and the presence of serum ANCA in 1,024 Italian subjects with various testing indications in a 10-year interval. Methods In this retrospective cohort study, a population of 6,285 patients (many of whom were subsequently excluded due to our criteria) who tested for ANCA at a single center in 10 years was considered, and life status and comorbidities of subjects were collected. We compared the overall survival of ANCA-positive and ANCA-negative patients by means of Kaplan-Meier curves, while a multivariable adjusted Cox regression was used to evaluate the association between the ANCA status and the outcome (death) in terms of hazard ratios (HR) with 95% confidence intervals (CI). Results The positivity of perinuclear ANCA (pANCA) increased significantly mortality (HR, 1.60; 95% CI, 1.10–2.32), while cytoplasmic ANCA (cANCA) positivity failed to show a significant association (HR, 1.43; 95% CI, 0.77–2.68). The increased mortality rate was observed for both pANCA and cANCA in patients suffering from rheumatic disorders. No association was found between mortality and anti-MPO (HR, 0.63; 95% CI, 0.20–2.00) or anti-PR3 (HR, 0.98; 95% CI, 0.24–3.96) after adjusting for confounders. Conclusions Serum pANCA and cANCA are independent negative prognostic factors in patients with concurrent autoimmune diseases.